ENGLISH USED BY MALE AND FEMALE FACEBOOK USERS IN THEIR POSTS - I Putu Andri Permana; Ida Bagus Gde Nova Winarta (Universitas Pendidikan Ganesha, 2020)
Language is a highly elaborated signaling system. The difference in using language between men and women when posting some words in certain social media, namely Facebook, has been researched by the researchers. The researchers choose this social media to collect data for their research because Facebook is one of the biggest social media in the world. This research is entitled English Used by Male and Female Facebook Users in their Post Based on the aforementioned background of the study, the problem of the research can be formulated as follows: (1) How do female and male Facebook users use lexicon in their posts? (2) How is the basic English sentence structure used by female and male Facebook users in their posts? In this research used some theories such as Language and Society by Hickey, Raymond. (2010) and basic sentence structure by Delahunty, Gerald P., and Garvey, James J. (2010)The method of this research covers data sources, data collection, and data analysis. The data of this research have been taken from Facebook. The method that has been used in collecting data was the method of library research. They were collected by reading the Facebook user’s post, by underlining and note-taking. The analysis was done by a descriptive method, to make the analysis clearer, all of the examples were completed with an explanation.